Hand Motor Cortex Excitability During Speaking in Persistent Developmental Stuttering - Sommer, Martin; Omer, Sherko; Wolff von Gudenberg, Alexander; Paulus, Walter (Frontiers in Human Neuroscience, 2019)
Persistent developmental stuttering (PDS) is a speech fluency disorder characterised by intermittent involuntary breakdowns of speech motor control, possibly related to motor cortex excitability. Whether motor cortex dysfunction extends into hand representations is unclear. We here studied task-dependent modulations of hand motor cortex excitability in 10 right-handed adults who stutter (AWS) and 13 age- and sex-matched fluent speaking control participants (ANS), covering a wide range of tasks in an exploratory study. Before, during and after a null speech/rest task, spontaneous speech, solo reading, chorus reading, singing, and nonverbal orofacial movements, transcranial magnetic stimulation was applied over the primary motor cortex and motor evoked potentials (MEPs) were recorded from the abductor digiti minimi muscle of either hand. In both groups, motor threshold was lower in the left than in the right motor cortex. During task performance, MEP amplitudes increased in both groups. A post-hoc comparison of spontaneous speech and nonverbal orofacial movements yielded an interaction of group by task with AWS showing higher than ANS MEP amplitude increase in spontaneous speech, but a lower than ANS MEP amplitude increase in nonverbal orofacial movements. We conclude that hemispheric specialization of hand motor representation is similar for both groups. Spontaneous speech as well as nonverbal orofacial movements are the orofacial tasks that merit further study. The excessive motor cortex facilitation could be reflecting a stronger activation of non-speech muscles during AWS’ s speech.